Answer:
1*65
5*13
that is all answers one through twelve
Step-by-step explanation:
I miss when everyone always said this
good times but ty for the points
Answer:
d=0
Step-by-step explanation:
Because multiplication is commutative, we can rearrange the expression however we want. So, let's put the constant expressions together, and the variable expressions together:
(3 x 4) x (d^-4 x d^4)
The first term is easy enough: (3 x 4) = 12
For the second term, when exponent terms have the same "base" (in this case, d), the exponents can be added together. So, the second term yields d^(-4 + 4) = d^0. Any number raised to the zero power equals 1, EXCEPT for the sole number of zero. 0^0 is undefined, but any other number raised to the zero power equals 1.
So, if d equals any number other than zero, the expression becomes
(12) x (1) = 12
The best way to express the answer would be that the expression equals 12 except that it is undefined if d=0
Answer: p=-7
Step-by-step explanation:
To solve for p, you want to isolate the variable, get p alone. You would use different algebraic properties to do so.
30+6p=7p+42-5
30+6p=7p+37
-7=p
p=-7